Research Data Management Support: Sharing Our Experiences. Issue 3 (3rd July 2017) - Morgan, Ann; Duffield, Nel; Walkley Hall, Liz
Abstract: The role of librarians in supporting researchers is ever changing and expanding. One of the most significant trends is for libraries to work in conjunction with other units in their institutions, for example information technology units and research offices, to support research data management (RDM). This is because RDM is a complex area involving work roles and expertise that librarians have not traditionally engaged with, and which in the past were largely left in the hands of researchers to manage themselves. Examples include data description and storage, data curation, data preservation, licensing and open access. This paper outlines how three South Australian academic institutions (the University of South Australia, University of Adelaide and Flinders University) have responded to this change. We describe how these libraries provide support (workshops, web pages, library guides and appointments); what tools and software packages are used; what additional skills library staff have had to acquire to provide support; and, what the outcomes were, what worked, and what did not work, and future plans.